Ground Deformations in the Corinth Rift, Greece, Investigated Through the Means of SAR Multitemporal Interferometry. (3rd December 2018) - Elias, P.; Briole, P.
Abstract: The Corinth Rift is one of the narrowest and fastest extending continental regions worldwide and has one of the highest seismicity rates in the Euro‐Mediterranean region. At its western termination, several active faults are located beneath the city of Patras and the surrounding area, a region of major socioeconomic importance for Greece. Displacement rates for the period 2002–2010 obtained from ascending and descending ASAR/ENVISAT multitemporal interferometry are combined with Global Positioning System measurements from permanent and campaign stations to produce a map of vertical and east‐west ground velocities. Cross sections are produced in order to quantify the deformation rates with higher precision. In the vertical, the motion combines tectonic deformation, urban subsidence, and subsidence due to deltaic sediments compaction. In the city of Patras and through the gulf of Patras, the northern continuation of the 2008 Movri earthquake fault is connected to the oblique transform zone of Rio. Further east, our observations suggest the existence of postseismic deformation at Aigion in the 15 years following the Mw = 6.2, 15 June 1995 Aigion earthquake. The inferred deforming zone, assuming a simple slow slipping model, is located at the western end of the 1995 fault, with radius 3.5 km, centroid depth 4 km, and cumulated postseismic moment representing 28% of the coseismic. Alluvial fan deltas subside due to their compaction with a gradient that increases toward the shore. Several of those deltas are located in the hanging‐wall of active faults. Plain Language Summary: The Gulf of Corinth, Greece, is a seismic area. Apart from moderate earthquakes striking often, additional geological phenomena, such as slow and continuous ground displacements, are occurring. Both are being induced by the movement of the tectonic plates. In many cases slow displacements are part of the seismic cycle occurring before an earthquake. The coast of Central Greece is moving away from the coast of northern Peloponnesus with a maximum velocity of about 1.5 cm per year. This study assesses the land displacements occurring due to tectonic activity of the area. This information is important to evaluate the seismic hazard and its impact on the socioeconomical activity of the region. Continuous ground displacements not associated to large earthquakes in the analyzed period are localized in the city of Patras, Rio, Aigion, and also in the surrounding areas. In the Mornos, near Patras and several other deltas, subsidence of no tectonic origin is detected. The maintenance and the expansion of the ground network are crucial for the uninterrupted monitoring of the geological phenomena. Our study can contribute to the awareness of the civilians, local authorities, and the state. Key Points: PSInSAR is combined with GPS to calculate vertical and east‐west ground deformation rate maps of the Corinth rift for the period 2002 to 2010 Several deformed zones are detected, quantified, classified and discussed; they are of deltaic and urban subsidence, and tectonic origin Aigion's fault shallow part is slow slipping due to postseismic relaxation; the Rio‐Patras fault is locked at shallows and creep at depth